Potensi kerugian ekonomi akibat biaya rawat inap dan rawat jalan pada balita yang mengalami obesitas sampai dewasa di Indonesia - Brigitte Sarah Renyoet; Drajat Martianto; Dadang Sukandar (Jurnal Gizi Klinik Indonesia, 2016)
Background: Nutrition and balance food very important for pregnant women so that the growth and fetal development can be optimal. Children, excess nutrients will be developed into a child obesity, if not be addressed urgently and left until the children become obese adults will lead to decrease productivity.Objective: To estimate the economic losses potential to obesity on the toddler when adults remain obesity and sick so that issued a maintenance cost (inpatient and outpatient).Method: This was a descriptive study with data processing of a variety of the relevant agencies as well as a secondary data in 2013. Data obtained is calculated using the formula derived from research Pitayatienanan et al. 2014 and correction factor of Guo et al. 2002.Results: Estimation of the economic losses potential due to low productivity is 3.492 – 8.717 billion rupiah/year (0,04 - 0,10%) of the total GDP in Indonesia.Conclusion: Economic losses potential due to the cost of obesity in Indonesia shows the loss of high enough, especially for developing countries. In addition to its prevalence of problems that high, loss also influenced by the changes disease patterns, maintenance of costs each disease comorbidities of obesity itself.